Freedom of Religion or Belief and Cultural Heritage Protection: Synergistic not Competitive - Thames, Knox (The review of faith & international affairs, 2022)
Unrealized synergies exist between freedom of religion or belief (FoRB) and cultural heritage protection (CHP), as these two related but rarely interacting fields of interest present novel opportunities for joint efforts on common concerns. New pathways to protect heritage and ensure worship rights can bring together international standards on CHP and FoRB with the praxis of individuals using historical sites with religious significance.